Frontispiece: Peptoid‐Directed Formation of Five‐Fold Twinned Au Nanostars through Particle Attachment and Facet Stabilization. Issue 14 (21st March 2022) - Jin, Biao; Yan, Feng; Qi, Xin; Cai, Bin; Tao, Jinhui; Fu, Xiaofeng; Tan, Susheng; Zhang, Peijun; Pfaendtner, Jim; Naser, Nada Y.; Baneyx, François; Zhang, Xin; et al.
Abstract : Nanoparticles The peptoid‐directed formation of five‐fold twinned Au nanostars through particle attachment and facet stabilization is reported by James J. DeYoreo, Chun‐Long Chen et al. in their Research Article (e202201980 ).